A Study on the feasibility of setting up a community pharmacy with patient counselling services - Arrojo, Reynold Obusan (Diliman, Quezon City College of Engineering, 2001)
The feasibility study involved characterization of Barangay Maimpis, San Fernando, Pampanga as a potential location for a community pharmacy. An increasing trend was observed in the population of the community and its surroundings. Two alternative sites were evaluated for the exact location of the pharmacy based on regulatory requirements and accessibility. A commercial space in the three-storey building at the corner of MacArthur Highway and Rizal Avenue in Barangay Maimpis was selected as the final site of the project. Regulations on the application for a license to operate (LTO) as a drug outlet were consulted at the Bureau of Food and Drugs. Results show that the project is technically feasible. Cash flow projections, pro-forma income statements and balance sheets were then obtained and used to evaluate the financial feasibility of the project. Results show that project is capable of generating enough cash with net profit and continue operations and service debts availed. Finally, cost-benefit and cost-effectivity analyses were used to analyze the socioeconomic feasibility of the project. Institution of the project as against the alternative of setting up a pharmacy without patient counseling services and status quo was found provide positive gains to the economy.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 221 : Project development and evaluation.
Keywords: Community pharmacy; Project management; Patient counselling services